FAKTOR INTERPERSONAL DAN FAKTOR STRUKTURAL DALAM EFEKTIFITAS IMPLEMENTASI CRM PADA PT KAI Commuter Line - Nurvi Oktiani (Widya Cipta - Jurnal Sekretari dan Manajemen, 2017)
The Business competitive with have rapid condition, should have been give attention for all the business activities, that have been doing, although all of the company must give attention for the factors will give opportunity in company or business to do compete, Customer Relationship Management or CRM is a tool or strategy will make increase for all the profitable and  Sales Volume transaction, and for the purpose of CRM is how to increasing customer satisfaction, this research use quantitative methods, with the simple random sampling , and use analysis factor toward the user of Commuter Line, the result of research describe two of analysis factor which give impact for the efectivities of CRM implementation consist of Interpersonal Factor and Structural Factor. Structural factor which must more give attention is The usage of service the custumer necessary , in despite of for Structural Factor is